PENGARUH KEBERAGAMAAN DAN KONTROL DIRI TERHADAP PERILAKU SEKSUAL SISWA MADRASAH ALIYAH MANAHIJUL HUDA NGAGEL DUKUHSETI - Heni Hidayatun-Ni’mah (EL-ADABI : Jurnal Studi Islam, 2022)
This study is a quantitative study that aims to empirically examine the influence of religion on sexual behavior, the effect of self-control on sexual behavior, and the influence of religiosity and self-control simultaneously on sexual behavior. The hypotheses proposed in this study are: first; there is an influence of religion on sexual behavior. Second; there is an effect of self-control on sexual behavior. Third; there is the influence of religiosity and self-control simultaneously on sexual behavior. The population of this study was all students of Madrasah Aliyah Manahijul Huda Ngagel, Dukuhseti District, Pati Regency, amounting to 305 students. Sampling was done by using the Cluster Random Sampling technique. Researchers took a sample of one class at random from each class spread over 3 classes, namely class X, class XI, and class XII. The results showed that there was a simultaneous influence of religiosity and self-control with the sexual behavior of the students of Madrasah Aliyah Manahijul Huda Ngagel Dukuhseti. This can be seen from the results of the F test calculation which shows a value of 19,083 with a probability level of 0.000 which is below an alpha of 0.005. Variables of religiosity and self-control were able to explain the sexual behavior variables of Madrasah Aliyah Manahijul Huda students by 50.8%, while the remaining 49.2% explained other variables not included in this model (not studied).